Exosomes as Crucial Players in Pathogenesis of Systemic Lupus Erythematosus. (20th July 2022) - Fei, Yue; Liu, Qi; Peng, Na; Yang, Guocan; Shen, Ziwei; Hong, Pan; Wang, Shengjun; Rui, Ke; Cui, Dawei
Abstract : Systemic lupus erythematosus (SLE) is a systemic autoimmune disease that affects multiple systems. Its clinical manifestation varies across patients, from skin mucosa to multiorgan damage to severe central nervous system involvement. The exosome has been shown to play an important role in the pathogenesis of autoimmune diseases, including SLE. We review the recent knowledge of exosomes, including their biology, functions, mechanism, and standardized extraction and purification methods in SLE, to highlight potential therapeutic targets for SLE.